Photoelastic Analysis of Two Different Cementless Femoral Stems for Total Hip Arthroplasty in a Canine Model - Kawamoto, Fernando Y. K.; Minto, Bruno W.; Diogo, Lucia M. I.; de Faria, Luis G.; Shimano, Antonio C.; Macedo, Ana P.; Camassa, José A. A.; Dias, Luis G. G. G. (VCOT Open, 2019)
Objectives The aim of this article was to analyse and compare internal stress generated at different points of a femoral photoelastic model after insertion and axial load application using two different cementless femoral stems for total hip arthroplasty in dogs: a collared stem combined with limited textured surface and absence of grooves and a collarless stem with fully textured surface and grooves.Methods Ten femoral photoelastic models, divided into two groups, were created using two different designs of cementless femoral stems. The models were submitted to axial loading on the femoral head in a universal test machine. The internal stress (kPa) around the femoral stems was evaluated at seven predetermined points using a transmission polariscope.Results The internal stress at the femoral calcar was larger in the models with collared stem combined with limited textured surface and absence of grooves (p < 0.05). No differences were identified between the groups in the other points (p > 0.05), corresponding to the tip of the stems and proximal lateral region of the femur.Conclusions The collar of femoral stem combined with the absence of grooves and more limited textured surface increase the axial load transmission to the femoral calcar, and in vivo, it may act to reduce complications, such as subsidence and stress shielding. However, other biomechanical tests and clinical evaluations must be performed to determine other important aspects for the implantation of these prostheses.
Keywords: orthopaedic implants; prostheses; biomechanics